Prediction of competition performance via selected strength-power tests in junior weightlifters - Ince, I.; Ulupinar, S. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Previous studies were limited to physical measurements or included very few performance test batteries, which has hindered the determination of the best tests for predicting competition performance in weightlifters. This study aimed to examine the relationships between body composition, Wingate anaerobic power, vertical jump height, isokinetic strength, handgrip strength, trunk strength, and competition performance and to determine the best predictors of competition performance in male junior weightlifters. METHODS: Sixty-seven male junior weightlifters (age 16.6±1.5 years, height 166.6±5.2 cm, body mass 67.0±9.3 kg) voluntarily participated in this study. After a national weightlifting competition, the participants were evaluated for anthropometric measurements, Wingate anaerobic power, isokinetic strength, vertical jump, handgrip strength, and trunk strength tests. The competition performance of the participants was calculated using the Sinclair equation and used as the dependent variable in statistical analysis. RESULTS: The correlations between the variables calculated from the five strength-power tests and the Sinclair score were significant (r=0.448 to 0.951, P=0.05). The regression model suggested that the best predictors of weightlifting performance were Wingate mean power, the countermovement jump with arm swing, and body fat percentage, which accounted for approximately 88% of the common variance associated with competition performance in male junior weightlifters. CONCLUSIONS: The results of this study showed that the predictors of weightlifting performance were Wingate mean power, countermovement jump with arm swing, and body fat percentage.